BLENDED LEARNING SEBAGAI METODE EDUKASI PENERAPAN PROTOKOL KESEHATAN DAN ENTREPRENEURSHIP PADA PEMANDU WISATA DI MASA PANDEMI COVID-19 - Cahyawati, P.N.; Saniathi, N.K.E.; Ningsih, N.L.A.P. (Buletin Udayana Mengabdi, 2023)
The COVID-19 pandemic has caused shocks to the economy, education, travel, and tourism sectors. The pressure on the tourism industry can be seen clearly with the decline in the number of domestic and foreign tourists. The impact of this pandemic is also experienced by partners in this service activity. Partners in this activity are tour guide groups in Bali. The Covid-19 pandemic makes a major impact on partners' income and employment. This activity seeks to provide education related to the implementation of health protocols and entrepreneurship development. The activity started with a discussion session, pretest, education program using the blended learning method, and posttest. Education about the implementation of health protocols was carried out offline, but entrepreneurship strategy was carried out online. The blended learning method can increase the knowledge of partners, which is marked by an increase in the average posttest score of 70 points. This value increased significantly, namely two times the mean value of the pretest. Thus, it can be concluded that education on health protocols and entrepreneurship by applying online and offline methods can increase the knowledge of tour guide groups in Bali. Keywords: health protocol,  entrepreneurship ,  blended learning , Covid-19